Environmental Implications of Liquid Natural Rubber Latex as a Sustainable Additive in Concrete: Effects on Mechanical Performance and Water–Cement Interaction - Hani Purwanti; Purwanto; Trias Widorini; Talitha Zhafira (Tecno Scientifica Publishing, 2026)
Increasing demand for ecologically friendly construction materials has promoted the use of renewable additives in concrete systems. This study investigates the influence of liquid natural rubber latex on the mechanical properties and water–cement interaction of conventional concrete with a focus on the environmental impact. Concrete mixtures were made using 0%, 5%, 7.5%, and 10% by volume of latex. Compressive and flexural strength tests were performed at 28 days to evaluate structural performance. The results show that increasing the latex content consistently decreases mechanical characteristics. Compressive strength dropped by roughly 10%, 18% and 26% and flexural strength reduced by 8%, 14% and 20% with 5%, 7.5% and 10% latex additions accordingly. This behavior is related to the involvement of latex as an extra fluid phase which affects the effective water–cement ratio, modifies hydration and leads to increased porosity and weaker bonding within the concrete matrix. From an environmental perspective, natural rubber latex provides advantages as a renewable and biodegradable resource that can lessen dependence on synthetic admixtures. However, the decline in mechanical performance suggests potential trade-offs, including reduced durability and greater material demand over the service life. The results imply that the latex application in concrete should be carefully regulated or supplemented with stabilizing materials to attain the best results. In conclusion, this study emphasizes the necessity to reconcile environmental benefits and engineering needs in the development of bio-based construction materials, especially in tropical settings.